2018
DOI: 10.1155/2018/4670834
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Rich Saline Activated Autophagy via HIF-1α Pathways in Neuropathic Pain Model

Abstract: Background Neuropathic pain is a chronic and intractable pain, with very few effective analgesics. It involves an impaired cell autophagy process. Hydrogen-rich saline (HRS) reportedly reduces allodynia and hyperalgesia in a neuropathic pain model; however, it is unknown whether these effects involve autophagy induction. Methods We investigated the relationship between HRS and cell autophagy in a neuropathic pain model generated by chronic constriction injury (CCI) in Sprague–Dawley rats. Rats received an intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 55 publications
2
23
0
Order By: Relevance
“…Moreover, studies uncovered that autophagy process was disrupted in neuropathic pain, localized on neurons, GAB-Aergic interneurons, astrocytes, microglia, and Schwann cells 2,37,38. Studies also indicated that treatments increased autophagy activity, prevented the onset and delayed the chronification of neuropathic pain, and ameliorated neuropathic pain-related behaviors 3,39…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies uncovered that autophagy process was disrupted in neuropathic pain, localized on neurons, GAB-Aergic interneurons, astrocytes, microglia, and Schwann cells 2,37,38. Studies also indicated that treatments increased autophagy activity, prevented the onset and delayed the chronification of neuropathic pain, and ameliorated neuropathic pain-related behaviors 3,39…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, intermittent hypoxia can also induce the increased HIF-1α expression [9]. Therefore, HIF-1α may participate in the intermittent hypoxia-induced autophagy activation [25]. Besides, HIF-1α can induce the over-expression of transcription factor p62.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, HIF-1α can induce the over-expression of transcription factor p62. Subsequently, it can release p62 from its binding with Bcl-2 protein, and the activated p62 can take part in forming autophagy [ 25 ]. In our study, we have found that HIF-1α was reduced in SCI model rats, which was contrary to the previous study [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that molecular hydrogen plays a protective role by modulating autophagy in multiple diseases and conditions, including sepsis 11, 12, 20, ischemia- reperfusion injury96-98, organ transplantation 70, 99-102, and pathological neuralgia 103-105 (Table 5). However, the regulation of autophagy by molecular hydrogen remains controversial, and the regulatory mechanism is very complex (Fig.…”
Section: The Biological Effects and Mechanisms Of Molecular Hydrogen mentioning
confidence: 99%
“…In addition, a number of studies have shown that HRS promotes autophagy in rats with neuropathic pain and plays a protective role103-105; the underlying mechanism of which is activation of hypoxia inducing factor-1 (HIF-1α) by HRS105 (Fig. 8D).…”
Section: The Biological Effects and Mechanisms Of Molecular Hydrogen mentioning
confidence: 99%